2017
DOI: 10.1039/c6ra25671f
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the binding interaction of andrographolide with the plasma proteins: biophysical and computational approach

Abstract: A phytochemical andrographolide is an anticancer agent with a stable conformation that strongly binds to the plasma proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 55 publications
(65 reference statements)
2
19
0
Order By: Relevance
“…The results were shown in ( Fig 7A–7L ), and are generated by using the Pymol software ( https://pymol.org ), and Ligplot ( www.ebi.ac.uk/thornton-srv/software/LIGPLOT ) is used to illustrate the two-dimensional interaction by hydrogen bond formation and hydrophobic interactions. The Binding constant values calculated computationally were in accordance with the values obtained experimentally [ 31 , 39 ].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The results were shown in ( Fig 7A–7L ), and are generated by using the Pymol software ( https://pymol.org ), and Ligplot ( www.ebi.ac.uk/thornton-srv/software/LIGPLOT ) is used to illustrate the two-dimensional interaction by hydrogen bond formation and hydrophobic interactions. The Binding constant values calculated computationally were in accordance with the values obtained experimentally [ 31 , 39 ].…”
Section: Resultssupporting
confidence: 82%
“…Using site specific markers we can understand the exact binding of ligand molecules to the specific domains of HSA. Hence, there are different site specific markers like lidocaine for domain I, phenylbutazone for domain II and ibuprofen for domain III [ 22 ] and using these markers the fluorescence was performed to analyze the specific binding domain of HSA on interaction with withanoside and withanolide derivatives [ 28 , 31 ]. Because of the structural and molecular similarity of four derivatives, all of them showed fluorescence emission quenching by displacing phenylbutazone, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…were shown in (Fig 6A-L), and are generated by using the Pymol software, and Ligplot is used to illustrate the two-dimensional interaction by hydrogen bond formation and hydrophobic interactions. The Binding constant values calculated computationally were in accordance with the values obtained experimentally [32,40].…”
Section: Molecular Dockingsupporting
confidence: 84%
“…Using site specific markers we can understand the exact binding of ligand molecules to the specific domains of HSA. Hence, there are different site specific markers like lidocaine for domain I, phenylbutazone for domain II and ibuprofen for domain III [22] and using these markers the fluorescence was performed to analyze the specific binding domain of HSA on interaction with withanoside and withanolide derivatives [28,32]. Kcal M -1 respectively (Fig 2 A-D).…”
Section: Displacement Studiesmentioning
confidence: 99%
“…9,10 This protein plays an important role in the transport, absorption, distribution, and metabolism of drugs in the body. 11,12 Crystallographic analyses have revealed that HSA is a 585-residue protein composed of three domains (I-III). Two subdomains (A and B) comprise an intact domain.…”
Section: Introductionmentioning
confidence: 99%